Pelatihan PMBA bagi Kader Kampung Keluarga Berkualitas Desa Membangun dalam Rangka Pencegahan Stunting - Indah Budiastutik; Marlenywati; Abdullah, Asrul; Karisma, Nova; Juliana Panemaan, Anita (J-Dinamika : Jurnal Pengabdian Masyarakat, 2024)
Stunting is a disorder that attacks the growth and development of children and babies caused by chronic malnutrition which is characterized by a body length or height that is below standard. Many factors underlie the high incidence of stunting, one of which is improper Infant and Child Feeding. The growth and development of toddlers is closely related to food intake which can have a major influence on optimizing the development and growth of infants and toddlers in 1000 HPK. The Kampung KB Membangun Desa is located in the Rasau Jaya Umum Village, Kubu Raya Regency, which is the focus of accelerating stunting reduction. The stunting rate in the district reached 27.8% in 2022. The stages of community service activities begin with coordination of activities with the coordinator, then continued with counseling and training. Community service is carried out using lecture, demonstration and question and answer methods supported by PMBA module media and equipment. Evaluation of counseling activities is carried out by providing a questionnaire sheet containing 10 questions. From the results of the SPSS analysis test, the respondents knowledge during the pre-test was 66.67%. After being educated, there was an increase in respondents knowledge during the post-test of 83.3%.